Development of Deep-Sea Anoxia in Panthalassa During the Lopingian (Late Permian): Insights From Redox-Sensitive Elements and Multivariate Analysis - Onoue, Tetsuji; Soda, Katsuhito; Isozaki, Yukio (Frontiers in Earth Science, 2021)
The end-Permian mass extinction (EPME) was the most severe mass extinction event of the Phanerozoic, and was associated with the development of global oceanic anoxia. The intensification of ocean anoxia preceded the EPME, but the degree of intensity and timing of oceanic redox changes in the mid-Panthalassa Ocean remain debated. Here we present the results of geochemical and multivariate statistical analyses of a late Guadalupian to Lopingian (middle–late Permian) bedded chert succession from the Iwaidani section, Japan, which preserves pelagic deep-sea facies from the ocean floor to the lower flank of a mid-Panthalassan seamount. The entire section yields a low manganese-enrichment factor (MnEF < 1), suggesting that suboxic conditions has appeared in the depositional environment already in the late Guadalupian. Enrichment factors of other redox-sensitive trace-elements (e.g., vanadium and uranium) and principle component analysis (PCA) of major element data show the development of suboxic to weakly anoxic conditions across the Guadalupian/Lopingian boundary. Subsequently, anoxic conditions, as inferred from enrichments in U, Mo, Ni, Cu, Zn, and Tl, were developed during the middle Lopingian. Extremely high concentrations of U and Mo (enrichment factors of ~6 and ~5500, respectively) indicate that H2S-rich euxinic conditions developed during the latest Lopingian and around the time of the EPME. The cause of the shift toward more reducing conditions in the early–middle Lopingian is unknown, but PCA results suggest that the euxinic conditions occurred in association with intensified continental weathering in response to a temperature rise during the ca. 200 kyr before the EPME.